2020
DOI: 10.3390/met10050558
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transition Layer on Properties of Tungsten-Tantalum (W-Ta) Laminated Composite

Abstract: Tungsten has many attractive properties, but its brittleness limits its application. Our team has found that the brittleness of tungsten can be greatly improved by combining the brittle tungsten with tantalum. Furthermore, we found that if a suitable transition layer is added between tungsten and tantalum, the properties of the composite will be further improved. In this paper, we studied the effect of different transition layers on the properties of W-Ta laminated composite to explore a suitable transition la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…However, present studies show that W/TiN/Ta-laminated composite plasticity will decrease, and interfacial cracking propensity will be increased due to the non-coherent interface between TiN and W [ 11 ]. Ti, V, Ni, and Ta were often used to toughen W in laminates or powder metallurgy materials [ 7 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, present studies show that W/TiN/Ta-laminated composite plasticity will decrease, and interfacial cracking propensity will be increased due to the non-coherent interface between TiN and W [ 11 ]. Ti, V, Ni, and Ta were often used to toughen W in laminates or powder metallurgy materials [ 7 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Laminated structure configuration (such as thickness or layer numbers) is the key factor to optimize the mechanical properties of laminated composites. Previous studies have shown that the deformation and fracture behaviors of the laminated composites may be affected by the laminated structure parameters [1,2]. Du et al [3] found that the elasticplastic deformation stage introduced between the soft and hard layers of Ti/Al laminated composites became more obvious with the decrease of the thickness of the Al layer.…”
Section: Introductionmentioning
confidence: 99%
“…Tungsten and its alloys have been used for many engineering applications such as in the aerospace, automotive, nuclear energy, materials processing, and defense industries. They are also considered attractive materials for high-temperature applications such as heating elements, rocket nozzles, heat shields, and combustion chambers [ 1 , 2 , 3 ]. This is due to the superior properties of tungsten such as high melting point (3420 °C), high thermal conductivity, high tensile strength, and high hardness [ 1 , 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…They are also considered attractive materials for high-temperature applications such as heating elements, rocket nozzles, heat shields, and combustion chambers [ 1 , 2 , 3 ]. This is due to the superior properties of tungsten such as high melting point (3420 °C), high thermal conductivity, high tensile strength, and high hardness [ 1 , 2 , 3 , 4 , 5 ]. In addition, due to its excellent radiation shielding properties, tungsten is also considered a promising plasma-facing material for future nuclear fusion reactors [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%